1177. Rapid, Non-invasive Detection of Invasive Mucormycosis Caused by Syncephalastrum monosporum Using Next-Generation Sequencing of Circulating Microbial Cell-free DNA in Plasma. (31st December 2020) - Sanacore, Melissa; Solh, Melhem M; Holland, H Kent; Bashey, Asad; Webster, Samuel; Morris, Lawrence; Solomon, Scott; de Vries, Christiaan R
Abstract: Background: Improving diagnostics have led to newly identified causes of invasive fungal infection (IFI) in immunocompromised hosts. Syncephalastrum spp. are Zygomycetes more commonly associated with skin infections and have only rarely been implicated as a cause of IFI(1). Next generation sequencing (NGS) for circulating microbial cell-free DNA (mcfDNA) in plasma offers a unique tool to diagnose rare causes of IFI (2, 3). Methods: Karius results were reviewed for Syncephalastrum detections with 2 identified at the same institution. McfDNA was extracted from plasma and NGS was performed by Karius, Inc. (Redwood City, California). Human sequences were removed and remaining sequences were aligned to a database of over 1, 400 pathogens. Organisms present above a predefined statistical significance threshold were quantified in DNA molecules per microliter (MPM). Chart review was performed for clinical correlation. Results: A 66 y/o male one month out of induction therapy for acute myeloblastic leukemia (AML) developed pneumonia. Although BAL was negative for mold and despite empiric antifungals, plasma NGS for mcfDNA showed S. monosporum at 562 MPM; the reference range is 0 MPM. Amphotericin was added to empiric posaconazole. The patient was discharged 10 days later and serial CT scans showed improvement. Repeat NGS mcfDNA 11 days later was negative. He underwent stem cell transplant (SCT) 4 months later. In a second case, a 66 y/o female with acute prolymphocytic leukemia was admitted for fever with neutropenia. A CT chest showed new multifocal, bilateral, nodular opacities. Despite negative BAL fungal culture and pretreatment with fluconazole, plasma NGS mcfDNA revealed S. monosporum at 575 MPM. She was treated with micafungin, amphotericin, and posaconazole with clinical improvement. Repeat NGS mcfDNA 8 weeks later was negative. Serial CT scans showed improvement over 5 months. She proceeded to SCT. Conclusion: Plasma-based NGS for mcfDNA enabled rapid, non-invasive detection of pulmonary mucormycosis caused by S. monosporum despite antifungal pretreatment and unrevealing invasive procedures in 2 patients with leukemia. The rapid identification of the specific etiology of IFI enabled targeted anti-fungal therapy and resumption of definitive oncological care including SCT. Table 1: Clinical Parameters Disclosures: Christiaan R. de Vries, MD, PhD, Karius (Consultant, Independent Contractor)Stanford University (Employee)